ANALISIS KEUNTUNGAN USAHATANI PADI SAWAH DI KECAMATAN ROKAN IV KOTO - Yulfita’Aini (Jurnal Ilmiah Cano Ekonomos, 2015)
of Rokan IV Koto in a single growing season. The method used is a survey method.The sample collection method is simple random sampling. The number of samples takenwere as many as 30 respondents. Data needed form of primary data and secondary data.The data collected, tabulated and analyzed. The analytical tool used is . Theresults showed that cultivation techniques were performed (land clearing, seeding, planting,weeding, maintenance, fertilization, pesticide use, harvesting and post-harvest). From theresults of this study showed that rice farmers districts Rokan IV Koto benefit each ha /planting period Rp. 6,390,508, -